Staying connected during the COVID-19 pandemic: highlights from the Paediatric and Congenital Interventional Cardiology Early-Career Society (PICES) 2020 activities - Góreczny, Sebastian; Whiteside, Wendy; Downing, Tacy; Aggarwal, Varun; Hiremath, Gurumurthy; Callahan, Ryan; Boe, Brian (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2021)
The Paediatric and congenital Interventional Cardiology Early-Career Society (PICES) was conceived in a hallway conversation during the 2011 Society for Cardiovascular Angiography and Interventions (SCAI) meeting in Baltimore, MD and was subsequently formally established in July of 2011 [1]. Since its inception, the organization has focused on promoting clinical education, fostering multicentre research collaboration, developing leadership skills, and promoting professional networking among the early-career (within 10 years of their training) paediatric/congenital interventional cardiologists as well as fellows-in-training. Membership is available free of charge to anyone in congenital cardiology training, congenital interventional cardiology training, or an interventional cardiology faculty early within their career. PICES is a special interest group of the SCAI, and multiple previous and current PICES executive committee members have served on the Congenital Heart Disease (CHD) council of the SCAI. Currently the society consists of more than 200 members with approximately 60% United States and 40% international representation.